Safety Assessement And Pharmacological Effect of Algal Oil Omega 3-6 Capsule Rich In Dha, Dpa, Epa From Oil of Heterotrophic Marine Microalga Schizochytrium mangrovei TB17 on the Experimental Animals - Thom, Le Thi; Ngan, Nguyen Hoang; Hong, Dang Diem (Academia Journal of Biology, 2018)
Recently, heterotrophic marine microalga Schizochytrium mangrovei has been shown to be rich in omega 3-6 fatty acids, mainly docosahexaenoic acid (DHA), ecosapentanoic acid (EPA) and docosapentanoic acid (DPA). These fatty acids play an important role on human health. In this article, we presented results of safety assessment and pharmacological effect of Algal Oil Omega 3-6 (AOO-3-6) which made from oil of S. mangrovei TB17 on the experimental animals after 90 days of use. The results of acute toxicity study showed that by oral administration of the AOO-3-6 on white mice at the highest dose of 15.27 g total of DHA, EPA, DPA / kg of whole body of mice/ day (the dosage was 113.63 times higher than the mice dose), the LD50 was not determined. It means that AOO-3-6 capsules was no signs toxicity. At doses of 78.4 mg and 352.8 mg of total of DHA, EPA, DPA/ kg of whole bode of rat/ day (effec-tive dose znd 4.5 times higher than the expected dose) for 90 continuous days on the mice didn’t affect the normal increment of body weight, hematological indices, biochemical indicators; function of liver and kid-ney; histopathology of liver, kidney, spleen of white rats. At the same time, at doses of 134.4 and 403.2 mg total of DHA, EPA and DPA/kg of body weight/day improved the ability to learn, remember on the mice. In addition, it also allowed building its reflexes sustainability in finding food to be faster with shorter reflectance time. As a result, AOO-3-6 capsules are safe and have the ability to improve memory, learning ability on the mouse which can be used for functional food for human health.